Socio-cognitive Impact of Artifact Replacement: The Curious Case of Amritsar Hand-Knotted Carpet Weaving in India - Kaur, Gagan Deep (Material Culture Review / Revue de la culture matérielle)

(untitled) (Cape Breton University Press, 2024)
What happens when an artifact gets replaced by another artifact in a practice? In what respects, this artifact replacement impacts users, tasks and practice? This paper discusses socio-cognitive impact of artifact replacement in Indian native craft practice, Amritsar carpet-weaving which used a code-based design representation (talim) till few decades ago which it inherited from its historical cousin Kashmiri carpet-weaving. However, this DR got replaced with a graph-based DR called naksha around India's partition in 1947. The cognitive impact of this replaced artifact on users in information retrieval, team communication and coordination, and social impact in terms of design creativity of industry is reported. The paper emphasizes including historical analysis of artifact-evolution over time and their impact on user-interaction while analysing artifacts so that one may go beyond giving static snapshots of their current profiles and associations.